Monitoring paddy rice cultivation adjustments in Northeast China through time series remote sensing and deep learning - Shihao Wang; Chong Huang; Lingxiao Huang; Xinliang Xu; Huading Shi; Qingbao Gu; Qiang Xue; Shiai Liu; Chenchen Zhang (International Journal of Applied Earth Observations and Geoinformation)
Northeast China is one of China’s most important rice production bases, contributing about one-fifth of the country’s rice production. In recent years, several agricultural policies have been implemented in Northeast China to adjust crop structures, driven by economic and ecological benefits. Timely monitoring of the changed pattern of rice cultivation is a prerequisite for policy assessment. Current paddy rice mapping methods are experiencing uncertainties due to confusion with wetlands and are highly parameter-dependent. To these, in this study, we developed a paddy rice mapping framework that integrates automatically generated training samples, time series features from key cultivation stages, and a deep learning model to improve paddy rice identification accuracy in Northeast China, which is a typical rice-wetland coexisting area. We produced 10 m paddy rice maps for 2019–2023 in Northeast China and examined their changes under agricultural policy implementation. The resultant paddy rice maps have high accuracies, with overall accuracies >0.97, producer’s accuracies >0.94, user’s accuracies ≥0.93, and F1 scores of ≥0.95, respectively. Our proposed mapping method effectively identified small patches of paddy rice and reduced confusion with wetlands. Paddy rice areas in Northeast China estimated in this study continued to decrease annually from 71.1 × 103 km2 in 2019 to 56.4 × 103 km2 in 2023. Hot spots of rice conversion to other crops were found in the Sanjiang Plain, mainly due to the Soybean Revitalization Plan. The rice cultivation expansion was mainly found in the Songnen Plain, resulting from policies on Rehabilitation and Utilization of Saline Soils. Observed changes in paddy rice plantation emphasize the importance and necessity of timely and continuous crop cultivation monitoring under the influence of agricultural policy adjustment.